Digital Technologies and Applications Proceedings of ICDTA 21, Fez, Morocco - Motahhir, Saad; Bossoufi, Badre (Lecture Notes in Networks and Systems, 2021)
XXVIII, 1836 p. 1135 illus., 840 illus. in color.